INFLUENCE OF INSECT AND SEED SAMPLE SIZE AND HEAT TREATMENT ON THE INFESTATION OF CALLOSOBRUCHVS CHINENS1S (L.) ON MUNGBEAN, VIGNA RADIATA (L) Wilczek *) - ELISA M. BucruANON1 (SEAMEO BIOTROP, 1997)
The influence of different insect and seed sample size and heat treatment on the infestation of bean weevil, Callosobruchus chinensis on mungbean,Vjg/m radiata (L.) Wilczek, was studied. Insect and seed sample size as well as varieties/genotype had significant influence in obtaining large responses in the number of eggs and progenies of the bean weevil. Use of at least 10 adult weevils to infest test samples containing at least 40 seeds for a 5-day oviposition period should produce reliable results when infesting mungbean seeds with unsexed weevils. Dry heat treatment was very effective in disinfesting mungbean seeds from the bean weevil in different developmental stages. It improved germination depending upon the condition of the seed before tr eatment and certain temperature limits. A suggested treatment for mungbean dismfestation using dry heat would be 60°C and 70°C for two-and one-hour treatments, respectively at 12% moisture content. For seeds in bulk, 60°C is much preferred.Key words: Callosobruchus chinensis/ Insect and seed sample size/Mungbean infestation/Heat treatment